Exploring the Impact of Green Finance on Sustainable Rural Development: Evidence From 283 Cities in China - Chuanjian Yi; Bo Xu; Kejun Lin (Discrete Dynamics in Nature and Society)
Green finance is of vital significance for global rural sustainable development. This paper aims to explore the impact of green finance on rural sustainable development. Based on panel data obtained from 283 prefecture-level cities in China over the period from 2004 to 2022, a rural sustainable development indicator system was constructed under the DPSIR framework. By employing a fixed-effects model, moderation effect analysis, and the spatial Durbin model, a role for green finance in rural sustainable development and its spatial effects is proposed. The results of these analyses reveal the following: (1) Rural sustainable development exhibits a cyclical expansion–contraction trend; (2) green finance promotes rural sustainability, confirmed by robustness checks; (3) environmental regulations and the digital economy play a positive moderating role in enhancing the impact of green finance on rural sustainable development; (4) in terms of spatial effects, green finance has a positive effect within the region but can exert a negative spillover effect on surrounding regions. Based on these findings, it is proposed that the layout of green finance should be strengthened, environmental supervision should be enhanced, and the digital economy should be promoted. Such recommendations represent critical measures which can serve as the foundation to stimulate rural sustainable development and provide valuable references for relevant policy formulation.